Effects of prescribed burning on undesirable plant species and soil physical properties on tallgrass prairies - Ungerer, James L. (Kansas State University, 2013)
Prescribed burning has been a common conservation practice on native prairie dating back to the days of pioneer settlement. Advantages include increased forage quality, reduction of undesirable plants, improved wildlife habitat, removal of accumulated dead plant litter and relatively low costs. While spring is the commonly accepted time to burn, little research has been conducted on late-summer and fall burning for specific objectives that include targeting undesirable plant species and measuring potential effects on soil physical properties. The first part of this study was to evaluate the effect that prescribed burning has on population dynamics of sericea lespedeza (Lespedeza cuneata [Dumont] G. Don), rough-leaf dogwood (Cornus drummondii Meyer), and additional woody species. Stem counts and cover estimates were taken from 20, 0.25-m[superscript]2 frames prior to and post-burn. Change in botanical composition, plant density, frequency, and Daubenmire canopy cover estimates were calculated. Sericea lespedeza plant frequency across all clay upland burns decreased 2.27% and increased 4.76% across all loamy/limy upland burns the first growing season post-burn. Dogwood densities increased 3.12 stems m[superscript]-[superscript]2 on spring burns compared to a decrease of 0.30 stems m[superscript]-[superscript]2 on unburned plots the first growing season post-burn. Changes in frequency of other woody species the first growing season post-burn showed significant interactions between burn treatment and ecological site, and between ecological site and year. A significant interaction between burn treatment and ecological site was found on total woody species plant composition changes two growing seasons post-burn for the first year of burn treatments. The secondary part of this study was to evaluate the effect of prescribed burning on soil bulk density and wet-aggregate stability. Soil samples were collected along the same line-transects used for vegetation sampling. Significant differences among mean weight diameters (MWD), percent water-stable aggregates (WSA), and WSA size fractions occurred between burned and unburned soils following burning in the fall of 2011. Monitoring plant and soil response to prescribed burning in different seasons may lead to adjustments being made in management of rangelands where sericea lespedeza, dogwood, and additional woody species occur.
Keywords: Sericea lespedeza; Rough-leaf dogwood; Density; Frequency; Daubenmire cover; Wet aggregate stability; Agronomy (0285); Range Management (0777); Soil Sciences (0481)